Phenotype-Driven In Silico Proficiency Testing Represents a Viable Approach for Undiagnosed Disorders by Exome Sequencing. - Schmidt, Ryan J.; Funke, Birgit; King, Ann; Halley, Jaimie; Hegde, Madhuri; Konnick, Eric; Lebo, Matthew; Mot, Nicole; Santani, Avni; Voelkerding, Karl; Leung, Marco L. (Archives of Pathology & Laboratory Medicine, 2026)
Context.--In silico mutagenesis can be performed to introduce variants into next-generation sequencing data. This method holds potential promise for proficiency testing since rare or novel variants can be modeled that are not found in available proficiency testing materials. Objective.--To determine whether in silico mutagenesis could be used as a viable proficiency testing methodology for undiagnosed disorders by exome sequencing. Design.--Laboratories performed exome sequencing on reference samples and uploaded raw sequence data files to the College of American Pathologists. These files were then mutagenized in silico to introduce variants, including those deemed to be causative for the clinical scenario provided. The laboratories processed the mutagenized files through their bioinformatic pipelines and performed interpretation to identify pathogenic and likely pathogenic primary and secondary findings. Responses were evaluated for concordance with intended responses. Results.--A total of 7 educational (nongraded) proficiency testing challenges were performed between 2018 and 2021. An average of 47 laboratories participated in each program, with each containing between 2 to 5 (average = 3.6) intended response variants. Intended response variant types included substitutions and small insertion/deletion variants. Participating laboratories returned 94.3% of intended response variants across all programs on average (per program range, 91.5%-97.3%). The percentage of laboratories that correctly returned all intended response variants for a program ranged from 70.0% to 96.7%. Conclusions.--In silico mutagenesis represents a suitable approach for graded intended response-based proficiency testing for exome sequencing that allows laboratories to assess both analytical and interpretative components of the test.